A systematic literature review of GHG emission declarations, limit values, and roadmaps for the decarbonisation of buildings - Marianne Kjendseth Wiik (Sustainable Futures)
The main objective of this paper is to systematically review the status and development of national greenhouse gas (GHG) emission declarations, GHG emission limit values, and decarbonisation roadmaps for buildings in literature. The systematic literature review (SLR) is carried out according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) checklist and uses the search database Scopus to identify relevant literature between 2016 and 2025. The following keywords were used: ‘whole life carbon’, ‘building’, ‘ghg emission’ and ‘limit value’. The search was supplemented with publications identified through snowballing. In all, 560 publications were identified, and 51 publications were included as full text reads in the SLR. The results are presented according to a bibliometric analysis, semantic mapping, and content analysis. The results show that the forerunners in implementing national GHG emission requirements for buildings include Denmark, France, Iceland, The Netherlands, Norway, and Sweden. There is also a plethora of methods, tools, and databases being used with varying system boundaries for building typologies, building parts, and life cycle modules, which hinders direct comparison of national limit values. The information gleaned from the SLR is used to outline steps towards establishing policy frameworks and national GHG emission requirements for buildings. Insights from early adopters provide valuable experience for other countries to develop their own policy frameworks and GHG emission requirements for buildings.